Recombinant N-acyl homoserine lactone-Lactonase AiiA(QSI-1) Attenuates Aeromonas hydrophila Virulence Factors, Biofilm Formation and Reduces Mortality in Crucian Carp - Zhang, Bao (Mar Drugs, 2019)
Quorum quenching (QQ) is a promising alternative infection-control strategy to antibiotics that controls quorum-regulated virulence without killing the pathogens. Aeromonas hydrophila is an opportunistic gram-negative pathogen living in freshwater and marine environments. A. hydrophila possesses an N-acyl homoserine lactone (AHL)-based quorum-sensing (QS) system that regulates virulence, so quorum signal-inactivation (i.e., QQ) may represent a new way to combat A. hydrophila infection. In this study, an AHL lactonase gene, aiiA was cloned from Bacillus sp. strain QSI-1 and expressed in Escherichia coli strain BL21(DE3). The A. hydrophila hexanoyl homoserine lactone (C6-HSL) QS signal molecule was degraded by AiiA(QSI-1), which resulted in a decrease of bacterial swimming motility, reduction of extracellular protease and hemolysin virulence factors, and inhibited the biofilm formation of A. hydrophila YJ-1 in a microtiter assay. In cell culture studies, AiiA(QSI-1) decreased the ability of A. hydrophila adherence to and internalization by Epithelioma papulosum cyprini (EPC) cells. During in vivo studies, oral administration of AiiA(QSI-1) via feed supplementation attenuated A. hydrophila infection in Crucian Carp. Results from this work indicate that feed supplementation with AiiA(QSI-1) protein has potential to control A. hydrophila aquaculture disease via QQ.